Televizyon yayıncılığında fenomen etkisi : Exxen örneği - Asma, Sevgi Nur (My University, 2023)
Bu çalışmada televizyon yayıncılığında çok değinilmeyen ve televizyonla arasındaki ilişkiye yönelik çok az çalışmaların yapıldığı televizyon ve fenomen ilişkisi incelenmiştir. Çalışmada fenomenlerin televizyon ve izleme alışkanlığı üzerine etkileri 3 fenomen içeriği üzerinden incelenmiştir. Konuşanlar, Kirli Çamaşırlar ve Enes Batur’la Buluşma programlarının neden izlendiğinden hareketle izleyicilerin tüketim biçimlerinde benimsedikleri izleme alışkanlıklarının Exxen’de nasıl bir dönüşüm geçirdiği ortaya konulmaya çalışılmıştır. Araştırma kapsamında 28 fenomen içeriği izleyicisi ve Exxen Genel Müdürü Ümmü Burhan ile yarı-yapılandırılmış mülakat yöntemi gerçekleştirilmiştir. Mülakat katılımcılarının, fenomen içeriğini izleme gerekçeleri Kullanımlar ve Doyumlar Yaklaşımı bağlamında değerlendirilmiş; fenomen içeriklerinin sosyal, bilgilendirici ve eğlendirici doyumlardan en çok sosyal doyuma ulaşmak için izlendiği sonucuna ulaşılmıştır. Çalışmada Exxen’in fenomenleri platforma dahil etmesiyle fenomenlerin abone sayısı, içerik sayısı, içerik çeşitliliği ve platformun yayıncılık anlayışının aktarılmasında katkı sağladığı sonucuna ulaşılmıştır. Günümüzde çok sevilen ve tüketilen fenomen içeriklerinin platforma geçmesiyle televizyonda yer alamayacak programların fenomenler aracılığıyla yayınlara dahil edildiği görülmüştür. Araştırma sonucunda katılımcıların, fenomen içeriğine bağlı ve etkileşimli bir izleme alışkanlığı geliştirdiği ortaya çıkmıştır.

In this study, the relationship between television and internet celebrity, which is not mentioned much in television broadcasting and where very few studies have been conducted on the relationship between television and it, has been Deciphered. In the study, the effects of internet celebrity on television and viewing habits were examined through the content of 3 internet celebrity. Based on the reasons why Konuşanlar, Kirli Çamaşırlar and Enes Batur'la Buluşma programs are watched, it has been tried to reveal how the viewing habits that viewers adopt in their consumption patterns have undergone a transformation at Exxen. Within the scope of the research, a semi-structured interview method was conducted with 28 internet celebrity content viewers and Exxen General Manager Umm Burhan. The reasons of the interview participants for monitoring the internet celebrity content were evaluated in the context of the Uses and Satisfactions Approach; it was concluded that the internet celebrity contents were monitored in order to achieve the most social satisfaction from social, informative and entertaining satisfactions. In the study, it was concluded that the internet celebrity contributed to the number of subscribers, the number of content, the variety of content and the transfer of the platform's publishing understanding by Exxen's inclusion of the internet celebrity in the platform. It has been seen that programs that cannot be included on television are included in broadcasts through phenomenals with the transfer of much-loved and consumed internet celebrity content to the platform today. As a result of the research, it was revealed that the participants developed an interactive viewing habit depending on the internet celebrity content.
The effect of internet celebrities on television broadcasting : The case of Exxen
Keywords: Exxen; Fenomen; Fenomen İçerikleri Television; Internet Celebrity; Internet Celebrity Contents; Television broadcasting; Television programs; Televizyon; Televizyon Programları; Televizyon yayıncılığı; Turkey; Türkiye